Czechoslovakia and Yugoslavia: The democratic hurdle of responsibility in a multi-ethnic society - Picheca, Giuseppe (International Journal of Contemporary Economics and Administrative Sciences, 2016)
The events of 1989 rewrote a term that was hidden for decades on the European political agenda: self-determination. Firstly as a need for the re-unification of the German States, then as a tool for boosting national emancipation movements. Czechoslovakia and Yugoslavia, two countries with multinational systems, witnessed the arrival of democracy as the result of their common project and territory: new foreigners, different borders. Both States were born at the end of the Austro-Hungarian Empire, had significant national minorities and faced a socialist experiment. But the regime change was diametrically different. Far from providing an explanation of the Yugoslav break up or the Velvet divorce, the comparative study analyzes similarities/differences in the élites addressing people/voters during the critical moment of regime change in 1989-1990. To what extent did the presence of an external dominator (Moscow) help the Czechoslovaks in behaving differently from the Yugoslavs? And on the other hand, how much did the absence of a greater enemy lead Yugoslavia to find guiltiness/innocence within its own people? The paper therefore focuses on the study of the presence/absence of “enemies” and their localization inside/outside the country, as two dichotomous variables that could have affected the political act of establishing new borders.